Mathematical skills in five-year-old preschoolers by gender - Limas Bravo, Lourdes Marivel (2020)
The purpose of the research is to establish the difference by gender in the mathematical competences of five-year-old preschoolers in an educational institution of Independence. To achieve this, the different skills in handling the basic elements of mathematics have been evaluated. Which contribute to the proper development of the reasoning processes. The methodology used corresponds to the quantitative approach, comparative level, basic and transversal. We worked with 80 preschool students evaluated with the Early Mathematical Assessment Test (TEMT). The results indicated that there are significant differences between five-year-old boys and girls. With obvious advantage in favor of boys compared to girls.